2014
DOI: 10.1016/j.apsusc.2014.07.168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO 2 addition on the microstructure and nanomechanical properties of Al 2 O 3 Suspension Plasma Sprayed coatings

Abstract: Versión / Versió:Preprint were used as starting materials. The coatings microstructure and phase composition were fully characterised using FEG-SEM and XRD techniques. Nanoindentation technique was used to determine the coatings hardness and elastic modulus properties.Results have shown that the addition of titania to alumina SPS coatings causes different crystalline phases and a higher powder melting rate is reached. The higher melted material achieved, when titania is added leads to higher hardness and elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 49 publications
5
10
0
Order By: Relevance
“…From the review of literature carried out, thermal spray variants bear promises to be applied on GCI brake discs and, in the near future, also keep pace with the regulatory demands that are certain However, the research on SPS wear resistance coating is still incipient and very few works have been conducted [154][155][156][157][158]. Early results by Tingaud et al [154] showed an improvement in the wear resistance of SPS Al 2 O 3 as well as low CoF (~0.39) by adding ZrO 2 in the matrix.…”
Section: Suspension Plasma Spray (Sps)mentioning
confidence: 99%
“…From the review of literature carried out, thermal spray variants bear promises to be applied on GCI brake discs and, in the near future, also keep pace with the regulatory demands that are certain However, the research on SPS wear resistance coating is still incipient and very few works have been conducted [154][155][156][157][158]. Early results by Tingaud et al [154] showed an improvement in the wear resistance of SPS Al 2 O 3 as well as low CoF (~0.39) by adding ZrO 2 in the matrix.…”
Section: Suspension Plasma Spray (Sps)mentioning
confidence: 99%
“…Besides, a filter with a mesh of 75 µm was placed before the injector to avoid clogging by agglomerates. This system has been set out in previous research [25,32]. AISI 304 stainless steel disks, with a diameter of 25 mm and 10 mm of thickness, were employed as substrates.…”
Section: Coating Preparation and Characterizationmentioning
confidence: 99%
“…Therefore, the great challenge of this first part of the research addresses the preparation and stabilisation of multicomponent aqueous suspensions of submicronic particles of Y-TZP/Al2O3/SiC (referred as SAZ). The literature on the preparation and stabilisation of each of these oxides or their combinations is abundant [22,[24][25][26][27]. There is also previous research on the preparation of highly concentrated, aqueous suspensions of SiC submicronic particles [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these coatings can be of significant interest for oil, gas, transmission and marine industries-which face corrosion problems. Due to the combination of wear-, oxidationand aggressive environments-resistance, the application of such coatings could protect parts working under severe conditions [11,[20][21][22][23][24]. Although papers report promising results regarding application of APS titaniaalumina based coatings for improvement of cavitation erosion resistance (CER) [18,25], it seems that influence of spray parameters has not been completely investigated.…”
Section: Introductionmentioning
confidence: 99%